Old finds, new data: Early Bronze Age human remains from Vučedol, eastern Croatia. (August 2021) - Zavodny, Emily; Solter, Ana; Balen, Jacqueline; Kennett, Douglas J.; McClure, Sarah B.; Novak, Mario
Highlights: Osteological and stable isotope analyses of human remains excavated in the 19th century. Early Bronze Age diets are more variable than in previous Eneolithic. Evidence of large-scale shifts in economic strategies at beginning of Bronze Age. Abstract: Vučedol is a site of major importance in the Carpathian Basin that provides valuable insight into daily life from the Early Neolithic to the Late Bronze Age. During the first archaeological excavations at the Vučedol–Streim Vineyard site in 1897, a total of 15 graves were excavated. Today eight skulls from this field campaign are curated at the Archaeological Museum in Zagreb. Combining modern methods with the study of archival materials, we present new results from archaeological, osteological, radiocarbon, and isotopic analyses of these individuals that demonstrate the dynamic cultural connections that existed during the Early Bronze Age in this region.